Pengaruh Struktur Modal Harga Batubara Acuan dan Profitabilitas Terhadap Nilai Perusahaan Sub Sektor Pertambangan Batubara yang Tercatat Pada Bursa Efek Indonesia Tahun 2012 – 2016 - Radian Peranginangin; Ferdinand Saragih (Sekolah Pascasarjana Perbanas Jakarta, 2019)
The purpose of this research is to analyze the impact of Capital Structure (DER), Coal Index Price (HBA), and Profitability (ROE) against Value of Firm (PBV) either partially or simultaneously for period 2012-2016. This study uses panel data from the secondary data source. The population in this study are coal mining sub sector companies listed in Indonesia Stock Exchange, Sampling using purposive sampling selected based on the criteria set as many as 18 companies. Analytical techniques used are descriptive statistical analysis and panel data regression analysis with the help of EViews’ version 7.0 program. The analysis result, showing that capital structure partially has no significant impact on company value, while the coal index price and profitability has positive and significant impact on company value. Simultaneously, capital structure, coal index price and profitability has positive and significant impact on company value with contribution of 40.90%.